Tracking the Spread of Sneaking Aliens by Integrating Crowdsourcing and Spatial Modeling: The Italian Invasion of Halyomorpha halys. (17th October 2018) - Maistrello, Lara; Dioli, Paride; Dutto, Moreno; Volani, Stefania; Pasquali, Sara; Gilioli, Gianni
Abstract: Polyphagous phytophagous organisms that shelter in man-made objects have a higher chance of becoming invasive fast-spreading pests, going undetected during phytosanitary checks and travelling with any type of goods. However, if the same organisms are also a household nuisance, they could be used in crowdsourcing surveys aimed at their early detection and to track their spread in real time. By participating in these surveys, people can be educated on the destructive potential of invasive species and on sustainable management options. However, in order to obtain good-quality data, useful to plant protection stakeholders, a one-to-one approach with people is crucial. The case study is the Italian invasion of Halyomorpha halys, among the most dangerous global crop-threatening pests. A 4-year survey that combined active search and a crowdsourcing approach made the tracking of its spread and investigation of its spatiotemporal dynamics possible, showing the functionality of coordinated multiactor approach in data collection.